¿Cambio climático o pantalla climática? Performatividad, creencias, realidad y verdad - Lara González, José David (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In recent years there has popularized the threat of severe climate change in the world. Similarly, it was announced due to serious disorders such global change in climate. In this paper we approach points to the management of these threats as dramatized and polarizing, given the capacity to generate new realities by the powers that be. We judge the role of these threats as distractors operated by the capitalist system of domination to divert the tensions, structured as a state and system of crisis, where the majority of human and the rest of nature have been severely torn. It is an invitation to reflect on the case and argues for restraint as a necessary tool to confront the conflict set.